FORMULATION DEVELOPMENT, CHARACTERIZATION, AND IN VITRO-IN VIVO STUDY OF ANTIHYPERLIPIDEMIC DRUG ROSUVASTATIN CALCIUM - SOLID LIPID NANOPARTICLES - Singh, Harjeet; Gupta, Ram Dayal; Gautam, Girendra (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this study was to formulate and optimize solid lipid nanoparticles (SLNs) for the enhancement of solubility and bioavailability of the poorly aqueous soluble drug rosuvastatin calcium. Methods: SLNs were prepared by slight modification of solvent emulsification-diffusion technique and analyzed for particle size, zeta potential, drug entrapment efficiency, in vitro drug release, stability, and pharmacokinetic studies. Rosuvastatin calcium SLNs were formulated using stearic acid as main lipid, poloxamer 407 as surfactant, and Tween 80 as cosurfactant. Results: All parameters were found to be in an acceptable range. Optimized formulation OR2 SLNs have shown mean particle size 115.49±2.97 nm with polydispersity index value of 0.456, zeta potential - 18.40 mV, 60.34% drug loading, and 97.16% drug entrapment efficiency. In vitro drug release was found to be 88.70±3.59% after 12 h with sustained release and was fitted with Higuchi model with a very high correlation coefficient (R2=0.9905). Transmission electron microscopy confirms that the SLNs of selected optimized formulation are circular in shape. Differential scanning calorimetry and X-ray diffraction confirm the formation of amorphous product. 1H nuclear magnetic resonance studies confirm the intermolecular hydrogen bonding between drug and lipid. Pharmacokinetic studies showed an optimized formulation OR2 SLNs enhanced bioavailability with 4.44-fold as compare to plain drug suspension. Optimized formulation OR2 SLNs have shown good stability at 25±2°C and 60±5°C relative humidity for 180 days. Conclusion: Thus, the current study can be useful for the successful development of optimized SLNs and able to enhance the bioavailability of poorly soluble drug rosuvastatin calcium.